Institutional review boards and health services research data privacy : a workshop summary (Online access: NCBI NCBI Bookshelf., 2000)
The Institute of Medicine (IOM) and the Committee on the Role of Institutional Review Boards in Health Services Research Data Privacy Protection hosted a workshop on March 13-14, 2000, to gather and to exchange information on the protection of human subjects in health services research (HSR). HSR examines the impact of the organization, financing and management, of health care services, on the access to, delivery, cost, outcomes and quantity of those services. The benefits of such studies include increased understanding of the effects of changing parts of the health care system, such as whether a change in the reimbursement policy for a particular class of drug has any effect on the health or quality of life of the participants. The major risk in such research is not physical harm, but risk resulting from improper disclosure of personal information, that is, a breach of confidentiality. Confidentiality can be protected by limiting access to data and strengthening protections of data handling. However, HSR can be conducted only if researchers have access to data. Thus, data privacy and data access are objectives that have to be balanced.